Ultrasound Assessment of Endothelial Function: A Technical Guideline of the Flow-mediated Dilation Test - Rodriguez-Miguelez, Paula (J Vis Exp, 2016)
Cardiovascular disease is the primary cause of mortality and a major cause of disability worldwide. The dysfunction of the vascular endothelium is a pathological condition characterized mainly by a disruption in the balance between vasodilator and vasoconstrictor substances and is proposed to play an important role in the development of atherosclerotic cardiovascular disease. Therefore, a precise evaluation of endothelial function in humans represents an important tool that could help better understand the etiology of multiple cardio-centric pathologies. Over the past twenty-five years, many methodological approaches have been developed to provide an assessment of endothelial function in humans. Introduced in 1989, the FMD test incorporates a forearm occlusion and subsequent reactive hyperemia that promotes nitric oxide production and vasodilation of the brachial artery. The FMD test is now the most widely utilized, non-invasive, ultrasonic assessment of endothelial function in humans and has been associated with future cardiovascular events. Although the FMD test could have clinical utility, it is a physiological assessment that has inherited several confounding factors that need to be considered. This article describes a standardized protocol for determining FMD including the recommended methodology to help minimize the physiological and technical issues and improve the precision and reproducibility of the assessment.